A Case of Sarcoidosis Associated With Anti–Tumor Necrosis Factor Treatment. (19th February 2015) - Baha, Ayse; Hanazay, Cigdem; Kokturk, Nurdan; Turktas, Haluk
Sarcoidosis is a systemic chronic granulomatous disease of unknown etiology. It predominantly involves the lungs but can affect many organs or tissues in the body, such as the lymphatic system, skin, eyes, and liver. Typical histopathological lesions are noncaseating granulomas in the affected organ or tissue. Indications, type of treatment, and duration of sarcoidosis treatment is currently debated. Despite studies showing that anti–tumor necrosis factor-α (TNF-α) treatment can successfully be used in refractory sarcoidosis, there are some case reports regarding the development of sarcoidosis with these agents. There have been reports of 47 anti-TNF-associated cases of sarcoidosis until 2012. The patient is a 54-year-old Caucasian male. During routine examinations of the patient who had been followed for psoriasis vulgaris for 20 years and who had been on several anti-TNF regimens thereafter, new pulmonary pathologies due to sarcoidosis were detected. We present here a case of sarcoidosis that developed after infliximab treatment and showed obvious radiologic regression with discontinuation of treatment. During anti-TNF treatment, it should be kept in mind that autoimmune and granulomatous diseases may develop and particular care should be given to patient follow-ups.